Relation of morphometric characteristics to land degradation in the Biyonga sub-watershed, Gorontalo Regency, Indonesia - Jaya, Risman; Murti, Sigit Heru; Adji, Tjahyo Nugroho; Sulaiman, Muhammad (Journal of Degraded and Mining Lands Management, 2024)
One of the crucial watersheds causing significant sedimentation in Lake Limboto is the Biyonga sub-watershed. This study aimed to examine and evaluate the morphometric characteristics of the watershed that contribute to possible erosion and land degradation hazards in the Biyonga sub-watershed. ALOS PALSAR (11.25 m), TERRASAR-X (5-10 m), and DEMNAS satellite images with a resolution of 8 m were employed, combining spatial analysis with a remote sensing approach and a Geographic Information System. Basic data of morphometric parameters were generated through basin morphometric analysis using Digital Elevation Model (DEM) image extraction. Then, the linear aspect, area, and relief parameters were defined by mathematical morphometric equations. The calculation results were interpreted into field data to confirm the relationship between watershed morphometric characteristics related to erosion and land degradation events. The results of the morphometric analysis showed that the flow density is a medium-textured criterion with a long elongation shape and an elongated flow pattern. Based on the relief aspect, the Biyonga Sub-watershed is in the form of moderate relief, has various characteristics with an average ratio, and has terrain that can trigger erosion and land degradation. This study has provided information that degraded land is not fully influenced by morphometric factors but due to poor land use and management systems, which accelerate erosion and sedimentation.